PENGALAMAN PERAWAT DALAM MERAWAT PASIEN TOTAL CARE DI RUANG ICU RSUD DR. R. SOSODORO DJATIKOESOEMO BOJONEGORO - Bayu Akbar Khayudin; Nurfain; Devi Retno Kusuma Hati (LPPM ISTeK ICsada Bojonegoro, 2022)
Abstract WHO reports that every year 9.8-24.6% of critically ill patients are admitted to the ICU per 100,000 population. In Indonesia, the mortality rate in the ICU reaches 27.6%. The high prevalence of critical patients is in line with the various problems that exist in the ICU to be resolved, so that deaths occur every year. Patients treated in the ICU are generally critical or total care patients who have different levels of needs. The purpose of this study was to determine the experience of nurses in treating total care patients in the ICU room of RSUD Dr. R. Sosodoro Djatikoesoemo Bojonegoro. This research design uses a qualitative method with a phenomenological approach. Data collection used in-depth interviews with face-to-face, involving 9 nurse participants who were in the ICU Room of RSUD Dr.R. Sosodoro Djatikoesoemo Bojonegoro. The results of this study get 8 themes. The conclusion of this study is that in caring for patients with total care, nurses provide nursing care by fulfilling basic human needs to medical needs, in carrying out nursing care, nurses experience obstacles in the form of lack of infrastructure and lack of nursing staff which causes the burden of nurses to increase, so that nurses have high responsibility for nursing care. in order to get an additional body of nurses and adequate infrastructure. Keywords: ICU Room, Nursing, Total Care